2019
DOI: 10.3390/jcm8101636
|View full text |Cite
|
Sign up to set email alerts
|

Papillary Vessel Density Changes after Intravitreal Anti-VEGF Injections in Hypertensive Patients with Central Retinal Vein Occlusion: An Angio-OCT Study

Abstract: Purpose: To investigate papillary microvascular changes in patients affected by macular edema due to Central Retinal Vein Occlusions (CRVO) after anti-Vascular Endothelial Growth Factor (VEGF) therapy. Methods: Prospective analysis of papillary and peripapillary vessel density (VD) changes in 18 eyes of 18 hypertensive patients affected by CRVO before and after the loading-phase of intravitreal Ranibizumab (IVR) injections. Data were quantitatively measured by optical coherence tomography (OCT) and optical coh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 45 publications
3
15
1
1
Order By: Relevance
“…Interestingly, recent study by Nicolai et al suggest the application of OCTA on peripapillary area to evaluate microvascular changes when the CRVO is complicated with macular edema. According to their study, peripapillary metrics can be more reliable data when the macular metrics are unreliable due to macular edema [20].…”
Section: Plos Onementioning
confidence: 99%
“…Interestingly, recent study by Nicolai et al suggest the application of OCTA on peripapillary area to evaluate microvascular changes when the CRVO is complicated with macular edema. According to their study, peripapillary metrics can be more reliable data when the macular metrics are unreliable due to macular edema [20].…”
Section: Plos Onementioning
confidence: 99%
“…We did not analyze factors associated with recurrence of ME during follow-up [ 20 ] and are unable to predict whether eyes with worse macular perfusion parameters are more prone to ME. Moreover, we did not analyze the peripapillary area, which may have led to different results, as a prospective study including 18 CRVO patients found increased peripapillary VD after anti-VEGF therapy [ 47 ]. We also did not consider healthy eyes as controls but we used the fellow eyes.…”
Section: Discussionmentioning
confidence: 99%
“…Nicola et al reported less W-disc and PP area VD in central retinal vein occlusion (CRVO) than normal fellow eyes, which are significantly increased after treatment [ 34 ]. Another study showed that mean RNFL thickness and W-RPC VD were significantly lower in the non-arteritic anterior ischemic optic neuropathy (NAION) group compared to normal group [ 35 ].…”
Section: Discussionmentioning
confidence: 99%